Breves aspectos jurídicos das principais modificações processuais penais realizadas pela lei Maria da Penha - Franco, Marlyo Sammyo de Brito Paiva (Universidade Federal Rural do Semi-Árido, 2018)
According to the World Health Organization (2002), the age group most vulnerable to domestic violence is between 15 (fifteen) and 40 (40) years of age. In the present work, some aspects of domestic violence in general, such as its history, will be addressed, as well as a number of draft laws prior to the creation of Law 11.340, the creation of the law known as Maria da Penha, and finally some criminal procedural changes resulting from creation of the law 11.340. A general analysis will be done on the main points, legal and their particularities, highlighting the importance of the discussion of the subject by the society. The purpose of this study is to analyze the criminal procedural changes resulting from the Maria da Penha Law: The exclusion of the incidence of Law no. 9.099 / 95, the possibility of a preventive custody order, the Unconditional Public Penalty action applied to light bodily injuries and the possibility of waiving the right of representation before the judge. Our approach was conducted from the perspective of the real pursuit of effecting the protection of the victim, observing how procedural changes can help to control the cycle of violence. The increase in the rate of domestic violence recorded in Brazil causes renewed concern and attention so that the population can effectively charge for the State's action, so that there are constant improvements of effective public measures, as well as their due maturation, in order to more and more we have real control, support, encouragement and prevention, and the appropriate punishment for the abuser.
Artigo Acadêmico
Keywords: Violência doméstica; Inovações processuais penais; Sociedade; Crime; Lei Maria da Penha; Domestic violence; Criminal procedural innovations; Prevention; Crime; Maria da Penha Law; CIENCIAS SOCIAIS APLICADAS::DIREITO